Pembentukan Lembaga Pengawas Perlindungan Data Pribadi Di Era Ekonomi Digital : Kajian Perbandingan Dengan KPPU - Matheus, Juan; Gunadi, Ariawan (Fakultas Hukum Universitas Muhammadiyah Sorong, 2024)
In recent years, the advancement of information and communication technology has made the circulation of personal data in Indonesia difficult to control, and cases of personal data breaches that harm consumers have often occurred. As a country that has specific regulations protecting personal data, there is a need for an overseeing institution to monitor the circulation of such personal data. However, up to this day, the government has not established this institution, causing uncertainty regarding the implementation of Law 27/2022. In conducting this research, the Author adopted a normative juridical research method, involving various approaches such as statute approach, conceptual approach, and comparative approach, with the aim of gaining a deeper and more comprehensive understanding of the analyzed issue. Based on the conducted analysis, the Author finds that the establishment of a Personal Data Protection Supervisory Institution would bring about numerous positive benefits, therefore this institution needs to be established promptly for Indonesia to achieve adequacy status. However, the form of this institution is still under debate as attaching it to the Ministry of Communication and Informatics may lead to a conflict of interest. In essence, Indonesia already has several independent state institutions, one of which is the Indonesia Competition Commission. Indonesia Competition Commissionis an independent state institution with a quasi-judicial model that cannot be intervened by any party in its handling, decision-making, or investigation of competition cases. Hence, drawing lessons from Indonesia Competition Commission, the Author's view is that the Personal Data Protection Supervisory Institution should ideally be established as an independent state institution due to the similarities it shares with Indonesia Competition Commission. Keyword : Personal Data Protection Law; Independent Supervisory Commission; Digital Economy